PERLINDUNGAN HUKUM TERHADAP DATA PRIBADI PENGGUNA LAYANAN PINJAMAN ONLINE ILEGAL - Variza Octifanny Rahmadianti; Dinda Putri Oktaviansjah; Beryl Nahdah Gunardi; Amanda Nadya Oktavia; Shafa Safira Diana (Jurnal Hukum Statuta, 2022)
Globalization makes technology development faster, as well as in the economic field. One of them is in lending and borrowing transactions which are available through online-based media, but in practice there are often reports of consumer personal data carried out by companies that are not registered with the Financial Services Authority (OJK). Based on these legal problems, the author uses a juridical-normative research method using a statute approach to answer the legal protection of the personal data of illegal lending service users in terms of the Information and Electronic Transaction Law and the Consumer Protection Act. The result of this research is that several cases have been found in the field which have been proven to be misuse of personal data from illegal online lending consumers. Misuse of personal data by online lending companies can be based on the Information and Electronic Transactions Act and the Consumer Protection Act.